Acute effects of alcohol septal ablation on systolic and diastolic left ventricular function in patients with hypertrophic obstructive cardiomyopathy. Issue 10 (1st May 2008) - Steendijk, P; Meliga, E; Valgimigli, M; Ten Cate, F J; Serruys, P W
Abstract : Objective: Hypertrophic obstructive cardiomyopathy (HOCM) often leads to heart failure, severe symptoms and death. Percutaneous transluminal septal myocardial ablation (PTSMA) by alcohol injection efficiently reduces left ventricular (LV) outflow tract pressure gradient and improves symptoms. We determined acute changes in haemodynamics and systolic and diastolic LV function after PTSMA. Methods: In 17 consecutive patients with symptomatic HOCM referred for PTSMA, the target vessel was determined by myocardial contrast transthoracic echocardiography. An over-the-wire balloon was inflated in the target vessel and multiple 0.5-ml alcohol injections were performed. LV systolic and diastolic function was assessed by online pressure-volume loops obtained by conductance catheter at baseline and acutely after the procedure. Results: In all patients except two, a single septal branch was treated using a total of 2.0 (0.5) ml ethanol per patient. The rest and post-extrasystolic gradient were significantly decreased after PTSMA (79 (38) to 14 (16) mm Hg and 130 (50) to 34 (33) mm Hg, respectively, both p<0.001). Ejection fraction decreased (78% (9%) to 67% (13%), p<0.001). Cardiac output, heart rate and stroke work were unchanged, but systolic and diastolic volume increased. End-systolic and end-diastolic pressure significantly decreased (166 (27) to 129 (26) mm Hg, p<0.001 and 25 (6) to 21 (7) mm Hg, p = 0.049, respectively). Significant rightward shift (p<0.001) and decreased slope (p = 0.041) of the end-systolic pressure-volume relation indicated reduced contractility, whereas diastolic stiffness, −dP/dtMIN, and tau were significantly improved after the procedure. Conclusions: PTSMA acutely reduced systolic function but promptly improved diastolic function with maintained cardiac output and stroke work. Improved diastolic function and increased end-diastolic volume compensated for the systolic loss and resulted in maintained haemodynamics.